Mizoram Planning and Development Department Draft Fifth Five Year Plan 1974-79 Vol. II - Planning Commission (Planning Commission, 1973)
The 4th Plan for road development in Mizoram was formulated by Govt, of Assam as this area was a part of Assam State at that time. There are- many schemes included in the 4th Plan where progress has been very poor. After fraction of Union Territory the relative importance of' some roads has changed considerably- and roads Programme of the in Five Year Plan arc reviewed and some read after examination which are found to be of less importance are proposed to be deferred for execution as they are only in the investigation stage or in the stage of initial, formatter cutting Some roods were also dropped from the state plan. and arc preps to be taken us by Border Roads Development Board as Central Scheme.
Mizoram Planning and Development Department
Mizoram Planning and Development Department
Keywords: Roads; Power; Inland Water Transport; water supply; Road Transport; General Education; Social Education; Education; Social Welfare; Tribal Research; Health; Housing; Urban & Rural Development; Labour & Labour welfare Statistics & Economics; Information & publicity; District councils.